MODEL LEARNING CYCLE 5E DALAM PEMBELAJARAN FLUIDA DINAMIS DI SMA (KAJIAN PADA KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR) - Habibah Zilul Isnani; Indrawati Indrawati; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2018)
AbstractThis research focused on the implementation of Learning Cycle 5E model indynamic fluid learning to students in grade XI. This research aimed to describe thescience process skills during use Learning Cycle 5E model and to determine theeffects of it to students’ cognitive achievement. The type of the research wasexperimental using post-test only control group design. Population were students ofclass XI MIPA in SMAN 2 Jember. Sample based on homogeneity test were class XIMIPA 1 as experiment class and XI MIPA 2 as control class. Data of science processskills was collected by using observation and students worksheet documentation.Science process skills was analyzed as descriptive with percentage analysis. Data ofstudents cognitive achievements were collected by using score of post-test. Theinfluence of Learning Cycle 5E model to students achievement was analyzed with ttest using SPSS 24. The results showed that the percentage of science process skillsin class XI MIPA 1 was 94,5%. There was a significant difference of students’cognitive achievement in experiment class and control class. This research can beconcluded: (1) students’ science process skill during learning process was very good;(2) the model significantly influenced to students’ cognitive achievement of dynamicfluid at grade XI MIPA 1 in SMAN 2 Jember .Key word: Learning Cycle 5E model, science process skills, student achievement.